Nanofibrous bio-inorganic hybrid structure formed through self-assembled peptide (FEFEFEFEFKFK) in distilled water and calcium acetate: article - Md Sah, Ili Natasha; Tan, Huey Ling; Veny, Harumi (2017)
This research is conducted in order to understand the synthesis of the hydroxyapatite (HAP) and to characterize the nanoparticles structure formed through selfassembled peptide, to study the synthesis of the nanofibrous hybrid structure formed through self-assembled peptide by using HAP, and to investigate and characterize the morphology of the nanofibrous formed through self-assembled peptide (FEFEFEFEFKFK) in water and salt (calcium acetate). This research is categorized into two parts: the synthesis and mineralization of HAP and the characterization of nanoparticles. Wet precipitation reaction was used in synthesizing Hydroxyapatite (HAP) sample at temperature of 80 ℃. Fourier Transform Infrared Spectroscopy (FT-IR) found that the HAP powder assigned with functional groups of PO₄³¯, OH¯, and CO₃²¯.